Risk modelling further implicates the angiogenesis pathway in anterior cruciate ligament ruptures. Issue 4 (3rd April 2022) - Rahim, Masouda; Lacerda, Miguel; Collins, Malcolm; Posthumus, Michael; September, Alison V.
ABSTRACT: The aim of this study was to explore the interactions between the interleukins and the angiogenesis signalling pathway, following a pathway-based approach. Statistical modelling tools were used to develop a preliminary polygenic risk assessment model for anterior cruciate ligament (ACL) ruptures, incorporating the angiogenesis signalling genes ( VEGFA and KDR ) and interleukins ( IL1B, IL6, IL6R ) which also function to regulate angiogenesis. Multivariate logistic regression analysis was used to identify the most informative contributors to ACL rupture risk from a range of eleven potential intrinsic risk factors: age, sex, BMI and eight genetic polymorphisms within five genes, namely, IL1B rs16944 C/T, IL6 rs1800795 G/C, IL6R rs2228145 C/A, VEGFA rs699947 C/A, VEGFA rs1570360 G/A, VEGFA rs2010963 C/G, KDR rs2071559 A/G and KDR rs1870377 T/A. A total of 232 asymptomatic controls (CON) and 234 participants with surgically diagnosed ACL ruptures, of which 135 participants reported a non-contact mechanism of injury (NON subgroup), were previously genotyped for the selected polymorphisms. The polygenic risk model identified the VEGFA rs699947 CC genotype ( p = 0.024, odds ratio (OR): 3.35, 95% confidence interval (CI): 1.17–9.62), VEGFA rs2010963 GC genotype ( p = 0.049, OR: 2.43, 95% CI: 1.00–5.87), age ( p = 0.011, OR: 0.97, 95% CI: 0.95–0.99) and BMI ( p = 0.009, OR:1.09, 95% CI: 0.57–2.11) as the most significant predictors of ACL rupture risk from the data included. The results of this study highlight VEGFA, age and BMI as biologically significant components of this network requiring further investigation in the context of musculoskeletal soft tissue injury risk. Highlights The findings of this study highlight the VEGFA gene, age and BMI as biologically significant contributors to ACL rupture susceptibility. Upon further validation of these risk factors, they may be included in genetic risk assessment tools to design pre-habilitation strategies, prescribe appropriate treatment strategies after injury or to assess how an individual is likely to respond to load. Polygenic risk models aid in highlighting the components of the complex ECM remodelling pathway requiring further investigation, using a multidisciplinary approach. VEGFA is a key angiogenic protein contributing to ECM homeostasis and may therefore have potential therapeutic implications that need to be explored.